2013
DOI: 10.7860/jcdr/2013/4579.2819
|View full text |Cite
|
Sign up to set email alerts
|

CRAO in Moyamoya Disease

Abstract: Moyo Moya Disease (MMD) is a rare, progressively stenotic condition of the intracranial arteries with various cerebrovascular manifestations. Ocular manifestations are seen very rarely and there are only few case reports of ocular perfusion anomalies. Central Retinal Artery Occlusion (CRAO) can be caused by atherosclerosis related thrombosis, carotid embolism, cardiac embolism, thrombophilic disorders, giant cell arteritis, etc. We are reporting a 26 years old patient with CRAO in the right eye, who was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…There have been 8 previous case reports on RAO associated with MMD 5–12 (Table 1, Cases 1–8). Half of these patients were teenagers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been 8 previous case reports on RAO associated with MMD 5–12 (Table 1, Cases 1–8). Half of these patients were teenagers.…”
Section: Resultsmentioning
confidence: 99%
“…Although MMD primarily affects the carotid artery in the ophthalmic artery bifurcation area, retinal vascular abnormalities have rarely been reported in MMD. 5–13 Until now, only a few cases on retinal artery occlusion (RAO) and retinal vein occlusion (RVO) have been reported. This study analyzed previously reported RAO and RVO cases along with three new cases of retinal vascular occlusion associated with MMD encountered at our institution.…”
mentioning
confidence: 99%
“…Ocular manifestations of MMD are rare. Central retinal artery occlusion,[ 2 ] central retinal vein occlusion,[ 3 ] and anterior ischemic optic neuropathy[ 4 ] have been reported in adults. MMD is also associated with optic nerve hypoplasia and chorioretinal coloboma.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from patients with cardiovascular emboli, CRAO is generally seen in the elderly population, especially those over 50 years old. However, the average age in the cases of MMD-associated CRAO mentioned above showed a younger tendency (26). When steno-occlusive and chronic ischemic changes involve the ophthalmic artery in MMD patients without the formation of collateral circulation, though rare, retinal artery occlusion may eventually be a complication.…”
Section: Retinal Vascular Occlusionmentioning
confidence: 96%
“…Obstruction of retinal vessels, particularly the central retinal artery, has been reported in several cases of MMD patients. A total of 6 cases reporting MMD associated retinal vascular occlusion are reviewed in this study ( Table 2) (24)(25)(26)(27)(28)(29). The chief complaint of almost all patients was acute vision loss.…”
Section: Retinal Vascular Occlusionmentioning
confidence: 99%